Strengthening Student Character Education Through Biology Learning in High School - A. Wahab Jufri; Tri Ayu Lestari; Jamaluddin Jamaluddin (Postgraduate, University of Mataram, 2022)
Strengthening character education through biology learning is a form of educator action that integrates character education values ​​in planning, implementing, and evaluating biology learning which is carried out intentionally and continuously to strengthen the character values ​​of students. This study aims to develop a character education-oriented biology learning tool and test its effectiveness on understanding character values ​​and mastery of biology concepts for high school students in West Lombok Regency. The method used is a mixed research method, namely development research methods to develop character education-oriented biology learning tools, and experimental methods to test the effectiveness of applying learning tools to understanding character values ​​and mastering biology concepts for high school students. The research sample amounted to 270 students who were determined by purposive random sampling technique. Data collection used research instruments in the form of expert validation sheets, feasibility assessment sheets, tests for understanding the values ​​of character education, and tests for understanding student concepts. The results showed that the character education-oriented biology learning tools were very valid and suitable for use in biology learning in high school. The results of the different concept mastery test are the mean score of the experimental class 69.78; and the mean score of the control class is 65.66 with a mean difference of 2.66. The results of the different test with the t test showed that there was no significant difference between the two mean scores. The results of the different test of understanding the values ​​of students' character education using the t-test obtained a mean experimental class score of 72.76; and the mean score of the control class is 70.10; means difference 2.66. Based on the t value, it was obtained that the mean scores of the experimental class and the mean scores of the control class were not significantly different